Papillary thyroid neoplasm: An incidental malignant nodule - Mahfujul Z. Haque; Michael Burcescu; Zirak Sajjad (Clinical Case Reports, 2023)
Key Clinical Message Papillary thyroid cancer (PTC), a common neoplasm originating from thyroid follicular cells, represents 85% of thyroid malignancy. PTC is known to metastasize to adjacent structures. Studies report that 5–15% of detected thyroid nodules represent malignancy; here, we report a 51‐year‐old woman with incidental thyroid nodules identified on the cervical spine.